Turbid coral reefs: Past, present and future—a review - Zweifler, A.; O’leary, M.; Morgan, K.; Browne, Nicola (MDPI, 2021)
Increasing evidence suggests that coral reefs exposed to elevated turbidity may be more resilient to climate change impacts and serve as an important conservation hotspot. However, logistical difficulties in studying turbid environments have led to poor representation of these reef types within the scientific literature, with studies using different methods and definitions to characterize turbid reefs. Here we review the geological origins and growth histories of turbid reefs from the Holocene (past), their current ecological and environmental states (present), and their potential responses and resilience to increasing local and global pressures (future). We classify turbid reefs using new descriptors based on their turbidity regime (persistent, fluctuating, transitional) and sources of sediment input (natural versus anthropogenic). Further, by comparing the composition, function and resilience of two of the most studied turbid reefs, Paluma Shoals Reef Complex, Australia (natural turbidity) and Singapore reefs (anthropogenic turbidity), we found them to be two distinct types of turbid reefs with different conservation status. As the geographic range of turbid reefs is expected to increase due to local and global stressors, improving our understanding of their responses to environmental change will be central to global coral reef conservation efforts.